Estimation of Evaporation from Different Meteorological Parameters - Singh, Ram; Prakash, Om; Khicher, M L (Annals of Arid Zone, 2016)
Simple correlations between different meteorological parameters and evaporation, measured from US Class A open pan evaporimeter, were worked out. The highest correlation value (0.85) was obtained with maximum air temperature, followed by wind speed (0.82). The coefficient of determinates for minimum air temperature, relative humidity and bright sunshine hours were 0.70,-0.56 and 0.15, respectively. The highest coefficient of determination was 0.92, when all these meteorological parameters were considered together.